2021
DOI: 10.4103/ajns.ajns_392_20
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of decompressive craniectomy for traumatic brain injury: An institutional-based analysis from Nepal

Abstract: Objective: Decompressive craniectomy (DC) is one of the commonly used treatment modalities for refractory intracranial hypertension after traumatic brain injury. The objective of this study is to assess the functional outcome following DC in closed traumatic brain injury based on Glasgow Outcome Scale (GOS). Materials and Methods: This is a retrospective study conducted at Nepal Mediciti Hospital, Nepal, from September 2017 to October 2019. Data of the patients who had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 25 publications
1
17
0
1
Order By: Relevance
“…In this study found majority were male (94.1%) and only 5.9% were female. These findings are well agreement with other studies Silva et al 2 Similar study Shah et al 13 reported 33 (71.7%) were male and 13 (28.3%) were female.…”
Section: Discussionsupporting
confidence: 92%
“…In this study found majority were male (94.1%) and only 5.9% were female. These findings are well agreement with other studies Silva et al 2 Similar study Shah et al 13 reported 33 (71.7%) were male and 13 (28.3%) were female.…”
Section: Discussionsupporting
confidence: 92%
“…This study was carried out to find on decompressive single stage bilateral craniotomy in case of patients suffering from traumatic brain injury. Irrespective of the fact that there is a lot of research going to find the pharmacological treatments related to traumatic brain injury but still it is a major health dilemma for people worldwide [12][13] . In order to standardize the surgical techniques and indications, there is a lot of study going on.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of TBI is brain oedema, increased ICP, reduced blood supply, reduced oxygen delivery to brain cells, and cell death. Therefore, the critical element in the management of severe head injury patients is to prevent secondary insult to brain cells, reduce brain oedema and ICP, and maintain blood, oxygen, and energy supply to the brain cells [5].…”
Section: Introductionmentioning
confidence: 99%